Wash Fit As A Complementary Tool For Industrial Hygiene In Primary Health Care Facilities: Case Study - Reza Jonatan; Galio RD Burdames; Ilmidin Ilmidin; Reza Hendrawan (Jurnal Ners, 2026)
Reliable water, sanitation, hygiene and waste services in health-care facilities (HCFs) are foundational to quality of care, infection prevention and control (IPC), and the Sustainable Development Goals (SDGs 3 and 6). In Jayapura, Papua Province, gaps in water, sanitation, hygiene (WASH), waste management in primary health centers (PHCs) compromise infection control, occupational safety, and quality of care. The WASH Facility Improvement Tool (WASH FIT), developed by WHO/UNICEF, offers a structured, risk-based approach to assess and improve these conditions. This study aims to evaluate the effectiveness of WASH FIT and promote the tool to mainstream WASH in the industrial hygiene context to improve health, safety, and environmental standards. An assessment using WASH FIT as a tool was conducted across 10 PHCs in Papua, combining scoring of key indicators (water, sanitation, hygiene, energy, waste, management) with structured observations, and technical documentation. WASH FIT assessment revealed significant shortcomings in key WASH indicators. Average scores were moderate to low: sanitation 55%, hygiene 66%, waste management 58%, and less than 60% had functional medical waste management systems. WASH FIT has proven to be an effective framework to improve occupational health standards in PHCs. Integrating WASH within an industrial hygiene lens offers a pathway to resilient systems in the broader context.